Electoral practice and the election commission of India: Politics, institutions and democracy - Katju, M. (Cambridge: Cambridge University Press, 2023)
The book offers an insight into the contribution of Election Commission to the Indian democratic process through its regulatory role in conducting elections between 1990 and 2019. It elaborates upon its interactions with pivotal state institutions - the Parliament, Supreme Court, and political parties - to streamline democratic procedures during this period. It demonstrates a comparison between important electoral procedures in India and other liberal democracies (the Canada, US, UK, South Africa among others) to highlight the role of electoral institutions in democratisation. It also studies the socio-political situatedness of the Election Commission as a body that moulds the political culture in India.
Keywords: Politics and Policy; Political Sociology; Politics and International Relations